Ectoparasite analysis in vaname shrimp in Padang Pariaman, West Sumatra, Indonesia - Elfrida, Elfrida; Rosida, Amrona; Lubis, Amelia Sriwahyuni; Munzir, Abdullah; Desmiati, Ira (Faculty of Marine and Fisheries, Universitas Syiah Kuala, 2025)
Ectoparasites pose a significant threat to the health and productivity of vaname shrimp (Litopenaeus vannamei) in aquaculture settings, particularly in tropical regions. This study aimed to assess the prevalence, intensity, and dominance of ectoparasites in vaname shrimp ponds in Padang Pariaman, West Sumatra. This study was conducted from March to May 2024 in vaname shrimp ponds in Padang Pariaman, West Sumatra. Sampling was carried out at five different pond stations, and water quality assessments were carried out. Ectoparasites were identified, and their prevalence, intensity, and dominance were measured. Station II had the highest prevalence (100%), intensity (69 ind/shrimp), and dominance of ectoparasites from all other observation stations. The dominant types of ectoparasites were Epystylis sp. (37.81%), Zootamnium sp. (18.65%), and Vorticella sp. (20.64%). Water quality at five Vaname shrimp pond stations showed significant variations, especially in pH, COD, and ammonia parameters, with some values exceeding the quality standard. Station V was identified as the most critical location with the highest COD (90.08 mg/l) and ammonia (0.188 mg/l) values and pH below the optimal threshold. It is important to implement better pond management strategies to improve shrimp health and productivity while minimizing the ectoparasites on aquaculture systems in tropical regions.Keywords:Vaname shrimpEctoparasitesAquaculture managementWater quality